Effects of foam rolling on hamstrings stiffness in damaged and non-damaged muscle states - Vatovec, Rok; Grandovec, Anja; Kozinc, Žiga; Voglar, Matej (Frontiers in Physiology, 2024)
The aim of this study was to examine the effects of foam rolling (FR) on hamstring muscles stiffness in both non-damaged and exercise-induced muscle damage (EIMD) states, using shear wave ultrasound elastography to measure changes in shear modulus. Fourteen healthy adults (25.5 ± 4.7 years) participated in a within-participant repeated measures design, with a 2-minute FR intervention applied on one leg and contralateral leg serving as a control. The damaging protocol encompassed maximal eccentric knee extensions performed on an isokinetic dynamometer and the Nordic hamstring exercise, consisting of 3 sets of 10 and 6 repetitions respectively. Measurement were taken at baseline and then 1h, 24h and 48h after the damaging protocol. The results indicated no significant time × leg interaction for shear modulus in biceps femoris, semimembranosus, and semitendinosus muscles in both non-damaged and damaged states. Notably, there was a significant increase in biceps femoris (p = 0.001; η 2 = 0.36) and semitendinosus (p < 0.001; η 2 = 0.44) shear modulus after EIMD, but no significant differences were found between the FR and control leg, which was also the case for muscle soreness, range of motion, and passive resistive torque (p = 0.239 -0.999 for interactions). The absence of significant changes post-FR intervention suggests a limited role of short-duration FR in altering muscle stiffness during recovery from EIMD. These findings contribute to the understanding of FR's role in muscle recovery. Although this was not directly investigated, our results suggest a predominance of central mechanisms rather than direct mechanical modifications in muscle properties. This research highlights the necessity for additional investigations to explore how FR interventions influence muscles in different states and to elucidate the mechanisms underlying these influences.